Advanced Glycation End Products and Malondialdehyde Serum Level Association with Nephropathy in Type Two Diabetic Patients - Alaa Abdullah Hassan; Sami A. Zbaar; Khedhair Abbas Khedhair (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim of the Study: Evaluate the relation of serum level of AGEs and MDA with the development ofdiabetic nephropathy in patient with type two diabetes mellitus and to evaluate the possible mechanismby which AGEs and MDA induce nephrotic complication in type two diabetic patients.Patients and Methods: This case-control study was carried out in Erbil city from the period startedfrom 1st of December 2020 to the end of March 2021. The study included 62 type 2 diabetic patients(31 patients nephropathy and 31 patients T2DM without nephropathy), their age between 40– 69 years,these patients who attended Rizgari General Hospital. The study also included 28 healthy controlindividuals defended as subjects who apparently haven’t any chronic diseases. Blood was collectedfrom each for determination of HbA1c level , AGE3 and MDA and RBS.Results: The study revealed that, the highest mean of RBS and HbA1c was recorded in DN groupfollowed by diabetic non-nephropathy and the control group. The study revealed that, the highest meanof UACR was recorded in DN group (258.6±28.56 mg/gm) followed by diabetic non-nephropathy(35.6±11.95 mg/gm) and the control group (20.39±1.72 mg/gm) (P<0.001). The study showed asignificant positive of AGEs and MDA with each of duration of DM, blood sugar, HbA1c and UACR.Conclusions: This study showed elevated of AGEs, MDA and Poor glycemic control were associatedwith diabetic nephropathy.